بلاد المهراج في العصر العباسي جزيرة جاوة أنموذجا 132-656هــ/749-1258م - إبراهيم، سفيان ياسين (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية, 2021)
تتناول الدراسة مملكة المهراج بوصفها إحدى المراكز الملكية (Royal Centries) إبان الخلافة العباسية، وماهية نظام الحكم والإدارة في التعامل مع الممالك والسلطنات التي تبعتها، من خلال عرض أنموذج سلطنة جاوة في التراث التاريخي العربي الإسلامي. يحاول البحث إظهار طبيعة النظم السلطانية، وامتزاجها بين النظم القديمة المتواترة، والنظم المتوافقة مع الطابع السائد بعد انتشار الإسلام. وتعرض الدراسة أيضا مظاهر الحياة العامة في سلطنة جاوة من إمكانات اقتصادية، وجوانب دينية وأخرى اجتماعية، امتازت بها السلطنة وعدت من سماتها البلدانية المتنوعة، ضمن وحدة مملكة المهراج العامة.
The study tackles the kingdom of Maharaja as one of the Royal centres during Abbasid Caliphate and the essence of governance and management system in dealing with the kingdoms and sultanates that follow it, throughout presenting the Sultanate of Java as a model in Arab-Islamic History. The study tries to show the nature of the sultanic orders and their relation to the frequent old orders and those orders, which are compatible with the common order after the prevalence of Islam. The study also presents the public phenomena of life in Java Sultanate including economic potentials, religious and social aspects which characterize the sultanate and are considered among the various country traditions in the kingdom of Maharaja.
Keywords: بلاد المهراج -- مملكة المهراج -- العصر العباسي -- الدولة العباسية -- جزيرة جاوة